Analyzing self-assessment of punching intensity between experienced and inexperienced boxing atheletes - Kommik, I.; Menzel, T.; Potthast, W. (ISBS Proceedings Archive (Michigan), 2023)
Due to the direct confrontation with a training or sparring partner, boxing and other martial arts represent a unique situation and the importance of accurate self-assessment, in which an incorrect self-assessment can lead to severe injuries for the participant himself or the sparring partner. The study aimed to investigate the self-assessment accuracy and repeatability between 26 experienced and inexperienced athletes for pre-defined punching intensities using a developed boxing monitoring sensor system. The results show considerable overestimated self-assessed punching intensities in the inexperienced in contrast to the experienced group revealing a substantial deficiency of punching intensity self-assessment.